The Effect of Health and Religious Beliefs on Consumer Consciousness of Using Halal Cosmetics - Sri Wahyuni Hasibuan; Yasir Nasution; Safaruddin Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The purpose of this study is to analyze in depth the effect of health and religious beliefs on consumer consciousness of using halal cosmetics. The subjects of this study are adult women who use cosmetics labeled halal and domiciled in Medan city. The number of samples is 100 people based on convenience sampling. Questionnaire is a data collection tool used in this study while the type is quantitative research. The analysis technique uses a variance-based SEM (PLS) approach with the Smart PLS 3 program. The findings of this study are that health and religious beliefs have a significant and positive effect on consumer consciousness of using halal cosmetics. The government, producers and cosmetics users must know that the concept of halal in cosmetics can be used as a global symbol to ensure the quality of the lifestyle of cosmetic consumers in the world. Because halal has positive scores for all lines of society. As healthy, clean, and protected from harmful ingredients. So this study recommends the need for the government which has the authority to consider halal cosmetic concepts to make regulations in producing cosmetics. Whereas for producers is a business opportunity or strategy to get more income. Because someone will be more aware of a positive after experiencing the effects of consuming something that can endanger her life.